Photoinduced processes in hydrogen bonded system: photodissociation of imidazole clusters - Poterya, Viktoriya; Profant, Václav; Fárník, Michal; Sistík, Lukás; Slavícek, Petr; Buck, Udo (The journal of physical chemistry. A, 2009)
The photodissociation of imidazole in hydrogen bonded clusters has been studied at photodissociation wavelengths 243 and 193 nm. Imidazole clusters of different mean cluster sizes n approximately 3 and 6 have been produced in expansions with He and Ar carrier gases, and the mean cluster sizes were determined by mass spectrometric and crossed beam scattering experiments. Simultaneously, the (C(3)N(2)H(4))(n) clusters were studied by ab initio calculations for n up to 4 molecules, confirming the hydrogen bond N-H...N motif in the clusters. The measured H-fragment kinetic energy distribution spectra exhibit a bimodal character similar to the KEDs found for the bare molecule. (1) At 243 nm the fast H-atoms originate from the direct dissociation process on the repulsive pi sigma* state, and the slow component results from the dynamics populating the vibrationally hot ground state via an S(1)/S(0) conical intersection. In the clusters the contribution of the slow component increases with the cluster size. The slow component is also dominant at the shorter wavelength of 193 nm, where the dynamics starts with the excitation of pi pi* state. It is shown that the slow component in our experiment is a product of subsequent two-photon absorption. We have proposed different mechanisms how the observed enhanced internal conversion can be rationalized. The increased stability with respect to the H-fragment dissociation in clusters can be caused either by hydrogen transfer in the N-H...N bond or by closing the pi sigma* dissociation channel as in the case of pyrrole clusters.
Keywords: kinetika; vodíková vazba; termodynamika; Thermodynamics; molekulární konformace; fotochemické procesy; Models, Molecular; Molecular Conformation; molekulární modely; Kinetics; Mass Spectrometry; Photochemical Processes; Quantum Theory; Hydrogen Bonding; hmotnostní spektrometrie; Imidazoles; imidazoly; kvantová teorie